Antipsychotics and mood stabilizers on risk for hepatic failure in people with schizophrenia and bipolar disorder - M.F. Tascón Guerra; M. Pérez Fominaya; M.V. López Rodrigo; A. Osca Oliver; M. Palomo Monge; A. Costoso López; V. Ros Font (European Psychiatry, 2022)
Introduction Patients with severe mental disease have a considerably shorter lifespan than the general population. The majority of psychiatric drugs are metabolized by the liver. Cytochromes play a central role, interactions between drugs are expected. Neuroleptics are frequently associated with weight gain, steatosis development, elevation of liver enzymes and rare acute cytolytic hepatitis, particularly with clozapine and olanzapine. Mood stabilizers, like Valproate classically gives mitochondrial steatosis with potentially important damages, and also possible acute liver failure.